THE EFFECT OF SHORT COURSE INTERVENTIONS TO IMPROVE KNOWLEDGE OF POSYANDU (INTEGRATED SERVICE POST) CADRES IN EARLY DETECTION OF STUNTING - Anditri Weningtyas; Puja Lina Ma'rufa; Dina Fauziah (Universitas Airlangga, 2023)
Introduction: Stunting is a cumulative growth and development disorder caused by inadequate nutritional intake, recurrent infectious diseases, or both. RISKESDAS data for 2018 recorded a national stunting prevalence of 30.8%, and Dilem Village, Malang Regency, is one of the loci for stunting in Indonesia in 2020. Anthropometry is a growth monitoring method for assessing children's nutritional status and one of the activities at Posyandu, is organized and led by cadres. Hence, it is important to increase the knowledge of Posyandu cadres to achieve the accuracy of children's nutritional status. Aim: The goal of this study was to determine the effect of short course intervention in the knowledge levels of Posyandu cadres in Dilem Village on early detection of stunting and anthropometric measurements of child. Method: The purpose of this study was to determine the effect of short course intervention in the knowledge levels of Posyandu cadres in Dilem Village on early detection of stunting before and after course This study was a pre-experimental study using one group of pre-posttest designs to assess the knowledge of 20 Dilem village cadres for early detection of stunting and correct anthropometric measurements before and after the intervention. Result: The results showed an increase of pre and posttest increase in score 16.5 points (p<0.001). Conclusion: So, it can be concluded that short course intervention can improve cadre’s knowledge on early detection of stunting.